Unravelling civil conspiracy - LEE, Pey Woan (Institutional Knowledge at Singapore Management University, 2018)
This article seeks to understand civil conspiracy through the lens of its historical rationale. It identifies that purpose to be the protection of public interests as the tort was originally fashioned as an extension of criminal conspiracy to counter serious social ills. For lawful means conspiracy, this rationale is exemplified by the requirement for improper or illegitimate motive whilst “unlawful means” serves the same function in the context of unlawful means conspiracy. Counter-intuitively, understanding the tort in this way provides a means of restricting the tort and reigning in its “revolutionary” tendencies. Recognising the tort’s policy-based foundation would, it is submitted, compel judges to articulate the policy considerations influencing their decisions and confine liability to cases where public harm is palpable and significant. This analysis further reveals that the conventional category of “unlawful means conspiracy” in fact comprises two species of liabilities: the first comprises “true” conspiracies concerned with securing public interests, while the second is a class of joint liability imposed on those who combine with another to commit an actionable wrong.